Given Equation is "z(z^2-xy) (px-qy) = x^4"
then "px-qy = \\frac{x^4}{z(z^2-xy)}"
comparing with general equation "Pp+Qq=R"
Then "\\frac{dx}{x} = \\frac{dy}{-y} = \\frac{dz}{ \\frac{x^4}{z(z^2-xy)}}"
Taking first two terms,
"\\frac{dx}{x} = \\frac{dy}{-y}"
Integrating both sides,
"\\int \\frac{dx}{x} = \\int\\frac{dy}{-y}"
"log (x) = -log(y) + logC"
"xy = C" (1)
Taking first and last term,
"\\frac{dx}{x} = \\frac{dz}{ \\frac{x^4}{z(z^2-C)}}"
Integrating both sides, "\\int x^3{dx} =\\int z(z^2-C){dz}"
"x^4 = z^4-2z^2C + C' = z^4-2xyz^2 + C'"
"x^4 -z^4+2xyz^2=C'" (2)
So required solution is
"f(xy,x^4-z^4+2xyz^2) = 0"
Comments
Leave a comment